Implementation of Addie Models to Determine the Learning Method to Improve Students' Ability to Read Map - Apriliani, Lina Herlina; Maryani, Enok; Ningrum, Epon (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The purpose of this study is to determine: (1) a method of learning that is appropriate to increase the ability of students to read a map using ADDIE models, (2) the ability of students to read a map before and after the implementation of the model ADDIE. The research method used in this research is descriptive qualitative. Data obtained using the test, and observation, which is based on basic competencies and indicators of achievement of competencies required to understand the fundamentals of mapping, P Remote Sensing, and Geographic Information Systems. The object of this research is class X IPS student of SMAN 23 Bandung in the academic year 2019/2020, with a sample of class X social studies 3 totaling 3 4 students. Results of the discussion: based on the Guttman rating scale when the score> 50%, then it was declared sufficient to be able to read the map with the distribution of indicators and percentages as follows on the indicators of students who were able to show the location of a particular place / geographical location had 80.5 % , students who were able to orient map (determine the direction on the map) amounted to 55.5% , students were able to interpret the symbols on the map 69.4% , students were able to reveal information on the map totaling 47.2%